Speciálněpedagogická diagnostika somatopedická Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Opatřilová, Dagmar (Masaryk University Press, 2018)
Title in English: Special pedagogical diagnostics in education of individuals with physical disability Limited and disordered movement or ability to move has an impact on the educational process and vocational training of the people with physical disability. It is not always possible to be educated at the place of living, because all schools have non barrier access and are not able to ensure optimal conditions for inclusive education. Immobility often means limited participation of pupil in some lessons, limits the choice of the leisure time activities and complicates independent movement (on a wheelchair) in the social environment due to the lack of the non-barrier access to pavements, shopping centres and cultural centres and offices. In some cases, persons with severe disability have limited life space and are often socially isolated. Together with the inclusive trends in the society it is necessary to create resources which enable to teachers, assistants and leisure time teachers to work with people with physical disability. The base of presented e-book is aimed on the support including the educational process and the aim is to summarise and present possible intervention and compensation. The studying text should make the orientation in the presented field easier and provide support to students and special needs teachers and to other specialists to solve the problems in the sphere of support of people with physical disability.